There Is No Carbon Transfer Between Scots Pine and Pine Mistletoe but the Assimilation Capacity of the Hemiparasite Is Constrained by Host Water Use Under Dry Conditions - Wang, Ao; Lehmann, Marco M.; Rigling, Andreas; Gessler, Arthur; Saurer, Matthias; Du, Zhong; Li, Mai-He (Frontiers in Plant Science, 2022)
Pine mistletoe is a hemiparasitic shrub that can produce its own photosynthates. There is a lack of knowledge about the interaction of mistletoe and host under varying environmental condition that might influence carbon gain and allocation. In a 13C-pulse labeling experiment with mature Pinus sylvestris (pine) infected by mistletoes grown in naturally dry or irrigated conditions, (1) mistletoe clusters were shielded from 13CO2 added, and (2) mistletoes or host needles were removed to manipulate the local assimilate and water availability. No 13C signal was found in shielded mistletoes, indicating no carbon transfer from the host to the mistletoe. When the pine needles were removed from girdled branches, no 13C signal was found in the host tissues, implying no carbon transfer from mistletoe to the host. However, mistletoes on needle-removed pine trees accumulated more labelled assimilates and had higher non-structural carbohydrate (NSC) concentrations only under naturally dry conditions but not in irrigated plots. Our results suggest that mistletoes show full carbon autonomy, as they neither receive carbon from nor provide carbon resource to the host trees. Moreover, the high assimilation capacity of mistletoes seems to be constrained by the host water use under dry conditions, suggesting that drought stress is not only negatively impacting trees but also mistletoes. Therefore, we conclude that the hemiparasites live on their own in terms of carbon gain which, however, depends on the water provided by the host tree.